Prevalence of Diabetes Among Community-Living Older Persons in the Philippines:: The FITforFrail Study - Giron, Maria Stella; de la Vega, Shelley Ann (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Objective. To estimate the prevalence of diabetes among Filipino older persons living in the community. Methodology. A cross-sectional analysis was done on a random sample of persons ages 60 years and older from the Focused Interventions for Frail Older Adults Research and Development Program (2018-2019). A diagnosis of diabetes was established by self-reported physician’s diagnosis or if the person was on any antihyperglycemic drugs. Results. The prevalence of self-reported diabetes was 20.5%, with no difference in age, sex, education, or body mass index between older persons with and without diabetes. The presence of 2 or more comorbidities was significantly more common among older persons with diabetes (p<0.001). Visual impairment (p<0.01), hypertension (p<0.001) and hyperlipidemia (p <0.001) were more frequent among those with diabetes. Conclusion. Diabetes is prevalent among community-living older Filipinos. Therefore, effective public health measures for diabetes prevention and management are needed for the ever-growing older population, who are at the highest risk for morbidity and mortality.